2011
DOI: 10.1016/j.mambio.2010.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of conifer seeds as major food resources to deer mice (Peromyscus maniculatus) and southern red-backed voles (Myodes gapperi)

Abstract: a b s t r a c tConifer seeds are a component of the diet of many rodents, but it is not known whether these seeds can be used as a major food source by rodents. Investigating this is critical to understanding how individual rodents utilize conifer seeds, and how their populations interact with seed production by coniferous trees. We examined the effects of conifer seed-diets on survival, body condition, food consumption, and gut morphology of deer mice (Peromyscus maniculatus) and southern red-backed voles (My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 61 publications
0
18
1
Order By: Relevance
“…Deer mouse demography was not positively affected by white spruce mast seeding, despite all contrary indications from individual‐level experiments (Lobo, Duong & Millar ; Lobo & Millar ; Lobo ) and our simulated spruce masting event. Conversely, we observed an unexpected delayed effect of subalpine fir mast seeding, where increased fall fir seed production did not influence overwinter or spring mouse demography, but instead enhanced summer survival, body masses and pregnancy rates of OW adults.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Deer mouse demography was not positively affected by white spruce mast seeding, despite all contrary indications from individual‐level experiments (Lobo, Duong & Millar ; Lobo & Millar ; Lobo ) and our simulated spruce masting event. Conversely, we observed an unexpected delayed effect of subalpine fir mast seeding, where increased fall fir seed production did not influence overwinter or spring mouse demography, but instead enhanced summer survival, body masses and pregnancy rates of OW adults.…”
Section: Discussioncontrasting
confidence: 75%
“…However, this is unlikely, given that PSCs in seeds are resistant to degradation over time (e.g. Shimada ), and the low nutritional value of fir seeds (Lobo & Millar ) is probably insufficient to enhance survival and breeding in rodents. It is more likely that the delayed effect of subalpine fir masting on deer mouse populations was mediated by population responses of invertebrate seed predators.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on food selection of small rodents showed that seeds of the genus Picea are preferred over Abies seeds (Schreiner et al 2000;Lobo et al 2009;Lobo and Millar 2011).…”
Section: Fir Versus Sprucementioning
confidence: 99%
“…Conifer tree seeds are an important component of the diet of many rodents and the major food resource for arboreal species, such as tree squirrels, in boreal and alpine conifer forests, manmade conifer stands and mixed broadleaf-conifer woods (Abbott and Quink 1970;Wauters and Dhondt 1987;Lurz et al 2000;Boutin et al 2006;Wauters et al 2008;Lobo and Millar 2011). Often, these rodents are not only seed predators, potentially reducing the tree's reproductive output, but also act as seed dispersers, potentially enhancing seedling establishment (reviewed in Theimer 2005;Steele et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Deer mice may also be positively influenced by deer density because of the natural disturbance induced by browsing, which may maintain attributes of early succession in forests (Potvin, Boots & Dempster, 2003;Tremblay, Huot & Potvin, 2006). Given that the diversity and abundance of major food resources like seedlings and insects (Desrosiers, Morin & Jutras, 2002;Lobo & Millar, 2011) appear highest at deer densities (Tremblay, Huot & Potvin, 2006;Brousseau et al, 2013), deer mice should mostly be favoured at these deer densities.…”
mentioning
confidence: 99%